Penguatan Literasi Musik Dasar dan Nilai Kebangsaan Siswa Sekolah Dasar melalui Metode Pembelajaran Notasi Berbasis Lagu Nasional - Laila Fitriah; Hengki Satria; Andi Idayani; Nike Suryani; Moza Paramitasari (Jurnal Pengabdian Masyarakat, 2026)
Music literacy at the elementary school level remains relatively underdeveloped, often due to limited teacher competence in music instruction and a lack of engaging learning media. This community service program aims to strengthen students’ basic music literacy while simultaneously instilling national values through a notation-based learning approach using Indonesian national songs. The program was conducted at SDN 115 Pekanbaru through a series of structured activities, including socialization sessions, participatory workshops, the utilization of interactive digital media, and continuous mentoring. The instructional approach introduced both staff (block) notation and numerical notation, enabling students to understand fundamental musical concepts more effectively. The findings indicate a notable improvement in students’ cognitive abilities in reading musical notation, as well as their psychomotor skills in accurately performing melodies. Furthermore, integrating national songs into the learning process contributed to strengthening students’ sense of nationalism, cultural awareness, and appreciation of diversity. This initiative also supports the development of the Pancasila Student Profile, particularly in fostering the value of global diversity (Berkebhinekaan Global). Therefore, the program demonstrates that music education can serve as an effective medium for both cognitive development and character building in elementary education.